Gambar Karakter Animasi Terhadap Peningkatan Asupan Makan Anak yang di Rawat di Rumah Sakit di Yogyakarta - Ida Mardalena; Weni Kurdanti (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
Undernourished among hospitalized patients known have related to the increasing of patient length of stay, the changes in clinical condition , increasing of over utilization of the hospital , and an increasing the risk of a complication. In the world there are around 60 million children with undernourished and 13 million children with worse undernourished7. The prevalence of undernourished in infants and children reached 31.8 %. The data from the various hospital in Indonesia, prevalence of undernourished is still high. Undernourished is the main health problems in the developing countries and is a contribute factors to more than 50 % of 10 up to 11 million kids that die every year, where the causes of death, has actually can be prevented6. Have been known that communication & education method can raise the nutrition status for chlidren. Research aims to determine the influence of a character picture animation with nutrition message on food intake among hospitalized children in Yogyakarta.This study involved children who hospitalized This research using quasi experiments with pretest and post test with control groups design. Involved 60 respondents who divided into 30 treatment respondents and 30 respondents as a control group.Statistical analysisusing dependent t-test with CI 95%. There are significant different food intake before and after using the character picture animation with p 0,0001 (CI:95 %). This research revealed that using a character picture animation with a message of nutrition can increased food intake on hospitalized children.